Teach Yourself VISUALLY Wireless Networking ( sách photocopy ) - Tidrow Rob (Visual, 2006)
view available networks, station firmware, wireless network settings, wireless network configuration, wireless network name, wireless network adapter, music engine, preferred network, upgrade file, upgrade firmware, wireless network devices, radio software, workgroup name, broadband modems, wireless hardware, wireless network connection, other network users, wireless router, wireless adapters, firmware updates, residential gateway, mobile computer, network adapters, firmware version, zero configuration